Targeted Immunotherapies in Gastrointestinal Cancer: From Molecular Mechanisms to Implications - Wang, Ding-Kang; Zuo, Qian; He, Qing-Yu; Li, Bin (Frontiers in Immunology, 2021)
Gastrointestinal cancer is a leading cause of cancer-related mortality and remains a major challenge for cancer treatment. Despite the combined administration of modern surgical techniques and chemoradiotherapy (CRT), the overall 5-year survival rates of gastrointestinal cancer patients in advanced stage disease are less than 15%, due to rapid disease progression, metastasis, and CRT resistance. A better understanding of the mechanisms underlying cancer progression and optimized treatment strategies for gastrointestinal cancer are urgently needed. With increasing evidence highlighting the protective role of immune responses in cancer initiation and progression, immunotherapy has become a hot research topic in the integrative management of gastrointestinal cancer. Here, an overview of the molecular understanding of colorectal cancer, esophageal cancer and gastric cancer is provided. Subsequently, recently developed immunotherapy strategies, including immune checkpoint inhibitors, chimeric antigen receptor T cell therapies, tumor vaccines and therapies targeting other immune cells, have been described. Finally, the underlying mechanisms, fundamental research and clinical trials of each agent are discussed. Overall, this review summarizes recent advances and future directions for immunotherapy for patients with gastrointestinal malignancies.